The effect of maternal risk factors during pregnancy on children's motor development at 5–6 years - Saros, Lotta; Setänen, Sirkku; Hieta, Janina; Kataja, Eeva-Leena; Suorsa, Kristin; Vahlberg, Tero; Tertti, Kristiina; Niinikoski, Harri; Stenholm, Sari; Jartti, Tuomas; Laitinen Kirsi (Elsevier, 2025)
Background and aims: Maternal diet and health may influence a child's later neurodevelopment. We investigated the effect of maternal diet, adiposity, gestational diabetes mellitus (GDM), and depressive/anxiety symptoms during pregnancy on the child's motor outcome at 5–6 years.
Methods: The motor performance of 159 children of women with overweight or obesity (pre-pregnancy body mass index 25–29.9 kg/m2 and ≥30 kg/m2, respectively) was assessed by the Movement Assessment Battery for Children – Second Edition (Movement ABC-2, total scores and subscales of manual dexterity, aiming and catching, balance) at 5–6 years. Higher percentiles denoted better motor performance with ≤15th percentiles for total scores being used as a cut-off for developmental coordination disorder (DCD). Diet (dietary patterns from three-day food diaries and fish consumption from a frequency questionnaire), adiposity (air displacement plethysmography), depression and anxiety symptoms (Edinburgh Postnatal Depression scale and the SCL-90/anxiety subscale, respectively) were assessed in early and late pregnancy. GDM was diagnosed with an oral glucose tolerance test at early or mid-pregnancy. Logistic and general regression models were used to analyse the associations.
Results: The mean percentiles for total scores of the Movement ABC-2 were 47.5 (SD 28.3), and 14.3 % of the children had DCD. A healthier maternal dietary pattern in early pregnancy associated with better motor performance in the child at 5–6 years (adj.mean difference = 9.80, 95%CI = 0.66–19.0). Higher maternal body fat mass both in early and late pregnancy (adj.OR = 1.07, 95%CI = 1.01–1.13, and adj.OR = 1.08, 95%CI = 1.02–1.14) and fat percentage in late pregnancy (adj.OR = 1.12, 95%CI = 1.09–1.24) were associated with higher odds for DCD. Increasing maternal depressive symptoms were associated with lower odds for impaired aiming/catching (early/late pregnancy adj.OR = 0.78, 95%CI = 0.65–0.93, adj.OR = 0.82, 95%CI = 0.70–0.96). GDM was not associated with the motor performance.
Conclusions: A healthier dietary pattern during pregnancy favoured children's motor development, while it was compromised by higher maternal adiposity. Promoting an overall healthy diet throughout pregnancy might support the motor development in children born to mothers with overweight or obesity. Our findings indicating that maternal depressive symptoms during pregnancy might associate with better motor performance in the child will require further research for confirmation.
ClinicalTrials.gov Identifier: NCT01922791.